Effect of Graphene Oxide Sealing on the Corrosion Resistance of Anodized Aluminum Oxide - Prifiharni, Siska; Senaputri, Yung Yung; Priyotomo, Gadang; Nikitasari, Arini; Kusumastuti, Rahayu; Musabikha, Siti; Bahtiar, Syamsul; Yanuar, Emsal; Suahimi, Lalu; Desiasni, Rita; Widyawati, Fauzi; Handayani, Murni (ASEAN Journal of Chemical Engineering, 2024)
Aluminum alloy materials are widely used in aerospace, construction industry, automotive, and other fields due to their low cost and typical properties, including high strength-to-weight ratio and good corrosion resistance. The role of the anodization process that forms anodic aluminum oxide (AAO) can improve corrosion resistance, but the aluminum surface is pivoted after the anodization process. This study was conducted to determine the effect of GO-sealed on the corrosion resistance of AAO. The results show that anodized aluminum with GO-sealed performs better corrosion resistance as indicated by higher Rporous and Rsolid values when compared to unsealed anodized aluminum. Furthermore, anodized aluminum with GO-sealed has a smoother surface and harder than unsealed aluminum. It is indicated by surface characterization and hardness test.